Immunization Status of NICU Graduates at a Tertiary Care Children's Hospital. (April 2017) - Macintosh, Janelle L. B.; Huggins, Leslie J.; Eden, Lacey M.; Merrill, Katreena Collette; Luthy, Karlen E. (Beth)
Abstract : Background: Approximately 500, 000 infants are born prematurely each year in the United States. Immunization of infants in a neonatal intensive care unit (NICU) set a precedence for future immunizations. Purposes: The objectives of this study were to determine the current rates of immunization and identify variables associated with immunizations of NICU graduates who were aged 60 days or older at time of discharge. Methods: This descriptive pilot study utilized retrospective paper medical record review in one tertiary children's hospital. The relationships between immunization status and study variables were examined using t tests and logistic regression. Results: Of 43 infants discharged at least 60 days of age or older from the NICU, 74.4% were fully immunized in accordance with American Academy of Pediatrics (AAP) recommendations. Significant predictors were age at discharge for immunization and steroid use for nonimmunization. Implications for Practice: Immunization needs to be a priority in order to give NICU infants every advantage regarding their future health status. Nurses need to implement hospital policies ensuring immunizations of NICU graduates. Implications for Research: Future studies should focus on samples from diverse hospitals and levels of NICUs. Qualitative studies exploring and describing parent and provider knowledge of current AAP guidelines will strengthen our understanding of potential barriers to immunization.